Women in scripture: a dictionary of named and unnamed women in the Hebrew Bible, the Apocryphal/Deuterocanonical books, and the New Testament - Carol Meyers; Toni Craven; Ross Shepard Kraemer (Michigan Houghton Mifflin Company, 2001)
Available for the first time in paperback, Women in Scripture is a landmark one-volume reference work exploring all the women mentioned in the Bible, named and unnamed, well known and heretofore not known at all. The book comprises more than 800 articles, written by the finest scholars in the field, that examine the numerous women who have often been obscured by the androcentric nature of the biblical record and by centuries of translation and interpretation that have paid little or no attention to them. The women of scripture are remarkably varied? from prophets to prostitutes, military heroines to musicians, deacons to dancers, widows to wet nurses, rulers to slaves. Here are familiar faces, such as Eve, Judith, and Mary, seen anew with the full benefit of the most up-to-date biblical scholarship. But the most innovative aspect of the book is the section devoted to the many women who in the scriptures do not even have names. In both scope and accessibility, Women in Scripture is an exceptional work. Combining rigorous scholarship with engaging prose, these articles on women in the Hebrew Bible, the Apocryphal/Deuterocanonical books, and the New Testament will inform, delight, and challenge all readers interested in the Bible.
Keywords: Biblical Studies (3ebOeGJ hOQGSGJ GdcJGH GdebOSs; Bible